Root-endophytes improve the ecophysiological performance and production of an agricultural species under drought condition. (18th August 2015) - Molina-Montenegro, Marco A.; Oses, Rómulo; Torres-Díaz, Cristian; Atala, Cristian; Zurita-Silva, Andrés; Ruiz-Lara, Simón
Abstract : Antarctic root-endophytes can improve the physiological tolerance and productivity of lettuce crops by means of several different physiological and molecular mechanisms, and could be a successful strategy to maximize water use efficiency and hence maintain an optimal yield in zones affected by desertification. Thus, application of antarctic root-endophytes to different crops could be a biotechnological tool for food security. Abstract: Throughout many regions of the world, climate change has limited the availability of water for irrigating crops. Indeed, current models of climate change predict that arid and semi-arid zones will be places where precipitation will drastically decrease. In this context, plant root-associated fungi appear as a new strategy to improve ecophysiological performance and yield of crops under abiotic stress. Thus, use of fungal endophytes from ecosystems currently subjected to severe drought conditions could improve the ecophysiological performance and quantum yield of crops exposed to drought. In this study, we evaluated how the inoculation of fungal endophytes isolated from Antarctic plants can improve the net photosynthesis, water use efficiency and production of fresh biomass in a lettuce cultivar, grown under different water availability regimes. In addition, we assessed if the presence of biochemical mechanisms and gene expression related with environmental tolerance are improved in presence of fungal endophytes. Overall, those individuals with presence of endophytes showed higher net photosynthesis and maintained higher water use efficiency in drought conditions, which was correlated with greater fresh and dry biomass production as well as greater root system development. In addition, presence of fungal endophytes was correlated with a higher proline concentration, lower peroxidation of lipids and up-/down-regulation of ion homeostasis. Our results suggest that presence of fungal endophytes could minimize the negative effect of drought by improving drought tolerance through biochemical mechanisms and improving nutritional status. Thus, root-endophytes might be a successful biotechnological tool to maintain high levels of ecophysiological performance and productivity in zones under drought.